High entropy metal sulfide phosphide electrolyte material and preparation method thereof

By using high-entropy metal thiophosphide electrolyte materials and using the solid solution effect of various metal elements, the problems of low ionic conductivity and poor thermal stability of solid electrolyte materials in solid-state batteries are solved, and efficient ion conduction and good thermal stability are achieved. It is suitable for electrolyte materials in solid-state batteries.

CN115312838BActive Publication Date: 2025-04-25BEIHANG UNIV

Patent Information

Application Number
CN202110495797.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-05-07
Publication Date
2025-04-25
Estimated Expiration
2041-05-07

AI Technical Summary

Technical Problem

The solid electrolyte materials in existing solid-state batteries have low ionic conductivity and poor thermal stability, which limits their application in solid-state batteries.

Method used

A high entropy metal thiophosphide electrolyte material is used, which is prepared by sintering from raw materials containing elements A, B, P and X. A is selected from metal elements in IA and/or IIA, B is selected from four or more transition metal elements, P is a phosphorus element, X is a non-metal element in VIA, and the molar ratio of A and B is between (1-4): (4-1).

Benefits of technology

It realizes high ionic conductivity and excellent thermal stability of high entropy metal thiophosphide electrolyte materials, and is suitable for solid-state electrolyte materials for solid-state batteries, meeting the application needs of solid-state energy storage devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115312838B_ABST
    Figure CN115312838B_ABST
Patent Text Reader

Abstract

The present invention discloses a high entropy metal sulfur phosphide electrolyte material and a preparation method thereof, wherein the high entropy metal sulfur phosphide electrolyte material is obtained by sintering a raw material containing A, B, P and X elements, wherein A is selected from at least one metal element in IA and / or IIA, B is selected from at least four transition metal elements, or B is selected from at least three transition metal elements and at least one main group metal element or metalloid element, P is a phosphorus element, X is selected from at least one non-metallic element in VIA, and the molar ratio of A to B is between (1 to 4): (4 to 1). The high entropy metal sulfur phosphide electrolyte material prepared by the present invention has high electrical conductivity, and shows a significant improvement in electrical conductivity compared to existing transition metal sulfur phosphorus compounds, can meet the needs of actual solid-state battery applications, and has excellent thermal stability, and has great application potential in the field of solid-state energy storage devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of new materials, and in particular to a high entropy metal sulfur phosphide electrolyte material and a preparation method thereof. Background Art

[0002] As a part of the all-solid-state battery, the solid electrolyte mainly plays the role of conducting ions and acting as a diaphragm. Solid electrolyte materials mainly refer to a class of materials with high ionic conductivity and no electronic conductivity. Because they simplify the use of battery electrolytes, electrolyte salts, diaphragms and binders, and have the characteristics of high energy density and rated power, they have become one of the hot spots in the field of battery energy in recent years. At present, a large number of fast ion conductors have been used in solid-state batteries, such as organic polymer materials, organic-inorganic composite solid electrolytes, and inorganic solid electrolytes. Although organic polymer materials (polyethylene oxide and its derivative systems, etc.) have the advantages of simple preparation and high safety performance. However, their ionic conductivity is generally low and their thermal stability is poor, which affects their application in solid electrolytes. Inorganic solid electrolytes are mainly divided into the following categories: oxide crystal solid electrolytes, sulfide solid electrolytes, sulfide glass and glass ceramic solid electrolytes, etc. Oxide solid electrolytes include NASICON structure LATP and garnet structure LLZO solid electrolytes. At room temperature, their ionic conductivity is very high, reaching 3×10 -4 S / cm, the conductivity of these oxide electrolytes can be improved by appropriate doping, but oxide electrolytes usually have high grain boundary resistance, poor mechanical strength, and high density, which hinders their application in solid-state electrolytes. In 2004, Avila, Ruiz, and Barahona et al. synthesized NiPS3 materials doped with Li, and then composited them with PEO to study the ionic conductivity of the material. The study found that after the addition of Li and PEO, the ionic conductivity was 0.13uS / cm, which is 2 times higher than the original NiPS3. Low ionic conductivity and high grain boundary resistance limit the application of many solid electrolytes in solid-state batteries. Summary of the invention

[0003] On the one hand, the present invention provides a high entropy metal sulfide phosphide electrolyte material, which is obtained by sintering a raw material containing A, B, P and X elements, wherein A is selected from at least one metal element in IA and / or IIA, B is selected from at least four transition metal elements, or B is selected from at least three transition metal elements and at least one main group metal element or metalloid element, P is a phosphorus element, and the X element is selected from at least one non-metallic element in VIA, and the molar ratio of A to B is between (1-4):(4-1).

[0004] In some embodiments, A is selected from at least one metal element selected from Li, Na, K, Mg or Ca; and / or, the transition metal element is selected from Ag, Au, Co, Cr, Cu, Fe, Hf, Mn, Mo, Nb, Ni, Pd, Rh, Ru, Sc, Ta, Ti, V, W, Y, Zn or Zr; the main group metal element is selected from Al, Sn, In or Bi; the metalloid element is selected from B, Ge or Si; and / or, X is S or Se.

[0005] In some embodiments, B is selected from transition metal elements of the fourth and fifth periods in groups VIIB, VIII, IB and IIB; and / or, B is selected from more than five transition metal elements, preferably, the elements in B are in an equal molar ratio; and / or, the molar ratio of P to X is 1:(1 to 3).

[0006] In some embodiments, the high entropy metal sulfide phosphide electrolyte material of the present invention has a two-dimensional layer structure and / or a single crystal structure.

[0007] On the other hand, the present invention also provides a method for preparing a high entropy metal sulfide phosphide electrolyte material, comprising: a sintering step, sintering a raw material containing elements A, B, P and X under vacuum or protective gas conditions to obtain a high entropy metal sulfide phosphide electrolyte material.

[0008] In some embodiments, the raw material containing A is a metal salt or a simple substance, and the raw materials containing B, P and X are simple substances.

[0009] In some embodiments, before the sintering step, a grinding step is also included for grinding and mixing the raw materials; preferably, the grinding method is ball milling.

[0010] In some embodiments, in the sintering step, the sintering temperature is between 500°C and 1200°C; preferably, between 700°C and 800°C; and / or, in the sintering step, the holding time at the sintering temperature is 10h to 100h; preferably, 40h to 60h.

[0011] Another aspect of the present invention also includes a battery containing the above-mentioned high-entropy metal sulfur phosphide electrolyte material; preferably, the battery is an all-solid-state battery.

[0012] Another aspect of the present invention also includes an electronic or electrical device comprising the above-mentioned battery.

[0013] At present, the performance research of materials brought by high entropy effect mainly focuses on the types of constituent elements and crystal structures in the field of alloy materials, and there is no report on the research of high entropy effect in transition metal sulfur phosphide compounds. The beneficial effect of the present invention is that it is found that "high entropy effect" can also be produced in transition metal sulfur phosphide, and the high entropy metal sulfur phosphide electrolyte material prepared by the present invention introduces at least one metal element (A) and at least four other elements, which has high ionic conductivity, and shows a significant improvement in ionic conductivity compared with the existing transition metal sulfur phosphide, which can meet the needs of actual solid-state battery applications, and has excellent thermal stability, and has great application potential in the field of solid-state energy storage devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 SEM photograph of a high entropy metal sulfide phosphide electrolyte material in one embodiment of the present invention.

[0015] Figure 2 XRD spectrum of the high entropy metal sulfide phosphide electrolyte material in one embodiment of the present invention.

[0016] Figure 3 STEM photo and diffraction spot pattern of the high entropy metal sulfide phosphide electrolyte material in one embodiment of the present invention.

[0017] Figure 4 TEM and element distribution diagram of the high entropy metal sulfide phosphide electrolyte material in one embodiment of the present invention.

[0018] Figure 5 TG curve of a high entropy metal sulfide phosphide electrolyte material in one embodiment of the present invention.

[0019] Figure 6 Ionic conductivity test curves of a high entropy metal sulfide phosphide electrolyte material and a comparative sample in one embodiment of the present invention.

[0020] Figure 7 A schematic diagram of the structure of a layered transition metal phosphorus sulfide compound in one embodiment of the present invention.

[0021] Figure 8 In one embodiment of the present invention, a CV curve test (a) of a battery containing a high entropy metal sulfide phosphide electrolyte material, a full battery cycle performance test (b) and a battery cycle test of different electrolyte samples (c) are shown.

[0022] Fig. 9 XRD comparison spectra (a) and scanning photos (b) of the high entropy metal sulfide phosphide electrolyte material before and after charging and discharging in one embodiment of the present invention. DETAILED DESCRIPTION

[0023] The technical solution of the present invention is described below by specific embodiments. It should be understood that the one or more steps mentioned in the present invention do not exclude the existence of other methods and steps before and after the combination step, or other methods and steps can be inserted between these explicitly mentioned steps. It should also be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. Unless otherwise specified, the numbering of each method step is only for the purpose of identifying each method step, and does not limit the order of arrangement of each method or limit the scope of implementation of the present invention. The change or adjustment of the relative relationship thereof can also be regarded as the scope of implementation of the present invention without substantial changes in the technical content.

[0024] The sources of the raw materials and instruments used in the examples are not particularly limited and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.

[0025] The technical concept of the present invention is to introduce five or more metals or transition metal elements (A and B) at the M position in transition metal sulfide phosphides (such as MPS3, where M is a transition metal element). Due to the different atomic sizes of different elements, lattice distortion will occur in the crystal structure of the material, affecting the electronic structure of the material and causing the material properties (such as mechanics, electromagnetism, high temperature resistance, corrosion resistance, etc.) to change, resulting in a "high entropy effect". Among them, at least one metal element (A) and at least four transition metal elements, or at least three transition metal elements and at least one main group metal element or metalloid element (B) are introduced into M, wherein the ions of the A metal element can serve as an ion conduction medium in the battery to provide A ion conduction. For example, the A metal element is Li, and the corresponding ions are Li + , is the ion conduction medium in lithium-based batteries (through Li + The conduction between the positive and negative electrodes of the battery realizes energy storage), thereby giving the high entropy metal sulfur phosphide electrolyte material of the present invention the conductivity of specific ions; similarly, the A metal element can also be elements such as Na, K, Zn, Mg, Ca, etc., and the obtained high entropy metal sulfur phosphide is used for battery electrolyte materials. In particular, the high entropy metal sulfur phosphide of the present invention is suitable for use as a solid electrolyte material in solid-state batteries. For example, the A element includes the Li element, which can be used as a solid electrolyte material with the performance of Li ion conduction and applied to lithium-based batteries (the battery electrode material contains metallic lithium or lithium ion compounds).

[0026] Example 1

[0027] In order to better illustrate the technical features of the present invention, the following is an example of a specific implementation method. In this example, a high entropy metal sulfide phosphide electrolyte material Li x (Fe 0.2 Co 0.2 Ni 0.2 Mn0.2 Zn 0.2 ) PS3 is used as an example for description, and its preparation steps include:

[0028] Batching step: according to the molar ratio of Li:Fe:Co:Ni:Mn:Zn:P:S=5:1:1:1:1:1:5:15, wherein the raw materials anhydrous lithium chloride, iron powder, cobalt powder, nickel powder, manganese powder, zinc powder, phosphorus powder and sulfur powder are weighed;

[0029] Grinding step: put the above raw materials into a planetary ball mill for ball milling and mixing, wherein the ball-to-material mass ratio is 1:20, the ball milling speed is 500 rpm, and the ball milling time is 20 hours;

[0030] Sintering steps: add the milled powder into a quartz tube with an inner diameter of 2 cm and a length of 20 cm, and use a vacuum tube sealing instrument to evacuate the quartz tube to 10 -3 Pa, and then sealed the tube, heated to 750°C in a muffle furnace at 2°C / min, kept warm for 60 hours, and then cooled with the furnace. The loose block obtained after cooling was taken out and ground, then washed with deionized water, and dried in vacuum at 60°C. The obtained product is the high entropy metal sulfide Li x (Fe 0.2 Co 0.2 Ni 0.2 Mn 0.2 Zn 0.2 )PS3 powder. The specific contents of Fe, Co, Ni, Mn, Zn, P, and S in the obtained product can be determined by ICP elemental analysis, and the content of Li element can be estimated by XPS elemental analysis. The specific chemical formula of the obtained product is Li 0.18 (Fe 0.19 Co 0.16 Ni 0.21 Mn 0.14 Zn 0.18 ) 1.04 S 2.8 By further adjusting the type and content of the doped B element through experiments, the amount of the Li element x can be adjusted between 0.01 and 0.5.

[0031] The powder product was tested by SEM, and the results were as follows: Figure 1 As shown in Figure 2, it can be seen that it has an obvious two-dimensional layer structure. The XRD test results are shown in Figure 2. Figure 2 As shown, it shows that the prepared product is a pure single-phase crystal structure (perovskite crystal). The scanning transmission electron microscope test photos and diffraction spot patterns of the product are shown in Figure 3 As shown, the obtained product has a two-dimensional layer structure and a single crystal structure. The element distribution test results of transmission electron microscopy TEM are shown in Figure 4As shown, it can be seen that the nanosheets have uniform distribution of Fe, Co, Ni, Mn, Zn, P and S elements, indicating that the transition metal elements are mutually dissolved and uniformly distributed. The obtained product was subjected to thermogravimetric analysis (TG), as shown in FIG. Figure 5 As shown, this material has good high-temperature thermal stability and still maintains its material and structure stability at a high temperature of 380°C.

[0032] The conductivity test of the product was carried out as follows: first, 300 mg of the sample was taken, and then a cold pressing mold with an inner diameter of 10 mm was used to press the tablet under a pressure of 4 MPa. Then, the ionic conductivity test was carried out using a stainless steel sheet sandwich electrolyte. The test method was to set the initial potential to 0 V, the scanning rate to 5 mV / s, and the range from 0.1 Hz to 10 6 Electrochemical impedance spectroscopy (EIS) tests were performed in the Hz range. x NiPS3、Li x FePS3、Li x MnPS3、Li x ZnPS3 and two-component Li x Fe 0.5 Ni 0.5 PS3 (two-dimensional single crystal compound, the preparation method of the comparative sample is similar to that of the high entropy metal sulfur phosphide of the present invention, except that the number of types of transition metal elements added is different), the test results are as follows Figure 6 As shown, it can be seen that compared with the single-component and double-component comparison samples, the high entropy metal sulfur phosphide Li x (Fe 0.2 Co 0.2 Ni 0.2 Mn 0.2 Zn 0.2 )PS3 has the smallest impedance value, and its room temperature ionic conductivity reaches 2.8×10 -4 S / cm. At the same time, as the temperature increases, the EIS impedance value decreases. When it is at 60℃, its ionic conductivity reaches 2.02×10 -3 S / cm, indicating that the high entropy solid electrolyte material of the present invention has excellent lithium ion conductivity and meets the requirements of practical solid-state battery applications (at room temperature, >10 -4 S / cm), which is much higher than that of the control sample.

[0033] In some embodiments, the batching step is as follows: raw materials of anhydrous lithium chloride, iron powder, cobalt powder, nickel powder, manganese powder, zinc powder, phosphorus powder and sulfur powder are taken according to a molar ratio of Li:Fe:Co:Ni:Mn:Zn:P:S=(1-20):1:1:1:1:1:5:15; anhydrous lithium chloride is added in excess in the batching to ensure the maximum amount of doping of metallic lithium element. Since anhydrous lithium chloride is a metal salt that is easily soluble in water, it can be removed by washing with deionized water, and no impurities will be introduced into the product.

[0034] Example 2

[0035] This example prepares high entropy metal sulfide Li 0.25 (Fe 0.25 Co 0.25 Ni 0.25 Mn 0.25 )PS3, the preparation method is similar to that of Example 3, except that in the batching step: according to the chemical formula Li 0.25 (Fe 0.25 Co 0.25 Ni 0.25 Mn 0.25 ) The stoichiometric ratio (molar ratio) of PS3 is Li:Fe:Co:Ni:Mn:P:S=1:1:1:1:1:4:12, wherein the raw materials of lithium metal, iron powder, cobalt powder, nickel powder, manganese powder, phosphorus powder and sulfur powder are weighed. In the sintering step, the temperature is raised to 600°C and kept at this temperature for 60 hours.

[0036] The same method as in Example 1 was used to prepare the high entropy metal sulfide Li 0.25 (Fe 0.25 Co 0.25 Ni 0.25 Mn 0.25 )PS3 test conductivity, its room temperature ionic conductivity reaches 1.8×10 -4 S / cm, significantly higher than the control sample (10 -7 ~10 -8 S / cm), but lower than Example 1.

[0037] In some embodiments, in the batching step: according to the stoichiometric ratio (molar ratio) of Li:Fe:Co:Ni:Mn:P:S=2:1:1:1:1:4:12, raw metal lithium, iron powder, cobalt powder, nickel powder, manganese powder, phosphorus powder and sulfur powder are weighed. In the sintering step, the temperature is raised to 800°C and kept for 40 hours to prepare a high entropy metal sulfur phosphide Li 0.5 (Fe 0.25 Co 0.25 Ni 0.25 Mn 0.25)PS3. Among them, metallic lithium is used as the raw material, part of the metallic lithium element is in the crystal structure, and part of it can be inserted into the two-dimensional layer. By adjusting the number and content of the doped B element, the amount of the Li element x can be adjusted between 0.01 and 3.

[0038] Since metal Na, K and Li belong to the same group of elements and have the same chemical properties, replacing element A with metal sodium or potassium to obtain a high-entropy metal sulfide phosphide containing metal sodium and potassium elements also has the same or similar technical effect in terms of electrical conductivity.

[0039] Example 3

[0040] This example prepares a high entropy metal sulfide phosphide electrolyte material Ca x (Fe 0.2 Co 0.2 Ni 0.2 Mn 0.2 In 0.2 )PS3, the preparation method is similar to that of Example 1, except that the element A is Ca element, and in the batching step: according to the chemical formula Ca x (Fe 0.2 Co 0.2 Ni 0.2 Mn 0.2 In 0.2 ) The stoichiometric ratio (molar ratio) of PS3 is CaCl2:Fe:Co:Ni:Mn:In:P:S=(1-5):1:1:1:1:1:5:15, wherein the raw materials anhydrous calcium chloride, iron powder, cobalt powder, nickel powder, manganese powder, indium powder, phosphorus powder and sulfur powder are weighed. In the sintering step, the temperature is raised to 900°C and kept for 60 hours.

[0041] Example 4

[0042] This example prepares high entropy metal sulfide Li 0.25 (Fe 0.25 Co 0.25 Ni 0.25 Mn 0.25 )PS2, the preparation method is similar to that of Example 1, except that in the batching step: according to the chemical formula Li 0.25 (Fe 0.25 Co 0.25 Ni 0.25 Mn 0.25 ) The stoichiometric ratio (molar ratio) of PS2 is Li:Fe:Co:Ni:Mn:P:S=1:1:1:1:1:4:8, wherein the raw materials of lithium metal, iron powder, cobalt powder, nickel powder, manganese powder, phosphorus powder and sulfur powder are weighed. In the sintering step, the temperature is raised to 600°C and kept at this temperature for 60 hours.

[0043] The present invention finds that the phenomenon that the high entropy metal sulfur phosphide electrolyte material exhibits a higher conductivity than a single-component or two-component comparative sample is attributed to the performance change brought about by the "high entropy effect". When five or more equal or approximately equal amounts of metals form a solid solution alloy, due to the different atomic sizes of different metal elements, lattice distortion is generated in the crystal structure of the material, affecting the electronic structure of the material and causing a change in conductivity. At present, the performance research of materials brought about by the high entropy effect mainly focuses on the types of constituent elements and crystal structures in the field of alloy materials, and there has been no report on the research of the high entropy effect in metal sulfur phosphide materials.

[0044] The present invention is based on the change of material properties brought about by the "high entropy effect", wherein B is preferably a metal or transition metal element that can form a high entropy alloy material, including: 22 transition metals (Ag, Au, Co, Cr, Cu, Fe, Hf, Mn, Mo, Nb, Ni, Pd, Rh, Ru, Sc, Ta, Ti, V, W, Y, Zn, Zr); 2 basic metals (Al, Sn); 6 lanthanide elements (Dy, Gd, Lu, Nd, Tb, Tm); 3 metalloids (B, Ge, Si), among which, more preferably, include: Al, Co, Cr, Cu, Fe, Mn, Ni and Ti, which appear in 1 Among more than 00 alloys, four elements (Co, Cr, Fe, Ni) each account for more than 70% in the high entropy alloy. In addition, common refractory elements (Mo, Nb, V, Zr) are also included; more preferably, B is selected from the fourth and fifth period transition metal elements in groups VIIB, VIII, IB and IIB, including Fe, Co, Ni, Mn, Zn, V, Cd, Cu, Ag, Pd or Ru, and these transition metal elements can be solid-dissolved with each other; it should be noted that B can also include some main group metal elements that can be solid-dissolved with transition metal elements, such as In in IIIA or Bi in VA.

[0045] In some embodiments, a more preferred implementation of the present invention is that B is selected from five or more metal or transition metal elements, and the elements in B are in an equimolar ratio to produce a "high entropy effect". The specific content of each element in the high entropy metal sulfide phosphide electrolyte material prepared by the present invention can be roughly obtained by elemental analysis test.

[0046] In some embodiments, the X element may also be Se or Te. These two elements are adjacent to the phosphorus element in the periodic table of chemical elements, and their non-metallic properties are close to those of the phosphorus element, so they are easy to replace the phosphorus element to obtain a high-entropy metal sulfur phosphide. More preferably, the X element is the S element, which has a non-metallic property greater than that of the Se element and is easier to replace the phosphorus element.

[0047] In some embodiments, the high entropy metal sulfide phosphide electrolyte material of the present invention exhibits a single crystal structure, and the formed crystal structure includes but is not limited to: perovskite type, rock salt type or phosphosulfide iron type. It should be noted that in addition to occupying the position of the transition metal element M in the crystal structure, when the high entropy metal sulfide phosphide electrolyte material of the present invention is a layered two-dimensional structure, A or B may also be embedded in the interlayer of the two-dimensional layered structure. For example, Figure 7 As shown in the figure, a schematic diagram of the crystal structure of a transition metal sulfur phosphorus compound (transition metal thiophosphite, MPS3) with a layered structure is given. When A and B occupy the position of M, the chemical formula of the high entropy metal sulfur phosphide can be expressed as A x B 1-x PS3, x = 0 ~ 1, when A and / or B are inserted into the interlayer, the chemical formula of the high entropy metal sulfide can be expressed as A x B y PS3, x+y>1.

[0048] In some embodiments, the molar ratio of the elements P:X=1:(1-3), resulting in the chemical formula A x B y PX 1~3 High entropy metal sulfur phosphide electrolyte materials also fall within the scope of the present invention.

[0049] Example 5

[0050] Based on the fact that the high entropy metal sulfur phosphide electrolyte material of the present invention has excellent electrical conductivity and thermal stability, it is particularly suitable for a solid electrolyte material for a solid-state battery. In this example, the high entropy metal sulfur phosphide electrolyte material prepared in Example 1 is assembled into a battery to test its electrochemical properties as a solid electrolyte material, wherein the thickness of the solid electrolyte material is controlled to be 0.5 mm.

[0051] 1. Assemble CR-2032 button test cells, using lithium sheets and stainless steel sheets as negative and positive electrodes, and conduct CV curve tests on the assembled cells. Set the open circuit potential as the initial potential, the highest potential as 7V, the lowest potential as -1V, and the scan rate as 1mV / s to conduct solid electrolyte electrochemical stability tests. The test results are as follows: Figure 8 As shown in a, it can be seen that the high entropy electrolyte material has good electrochemical stability in the range of -1V to 7V.

[0052] 2. Assemble into a CR-2032 button-type full battery, wherein the lithium sheet is the negative electrode and the lithium iron phosphate is the positive electrode. The full battery of the present invention is subjected to electrochemical testing at room temperature and a current density of 0.2C, and the test results are as follows: Figure 8As shown in b, it can be seen that after 60 cycles of charge and discharge, its specific capacity can be maintained at 132 mAh / g, which shows that the high entropy electrolyte material of the present invention has excellent lithium ion conductivity and cycle stability.

[0053] 3. Assemble into CR-2032 button-type symmetrical battery (hereinafter referred to as the symmetrical battery of the present invention), under the same conditions, Li x NiPS3、Li x FePS3、Li x MnPS3、Li x ZnPS3 and Li x Fe 0.5 Ni 0.5 PS3 was used as a comparative sample (comparative symmetrical cells 1, 2, 3, 4, and 5, respectively; the preparation of the comparative samples is similar to the preparation method of the high entropy metal sulfur phosphide electrolyte material of the present invention, except that the element types of the raw materials are different). The symmetrical cell of the present invention and the comparative symmetrical cells 1, 2, 3, 4, and 5 were subjected to a 0.05 mA / cm 2 The electrochemical test was carried out at a current density of Figure 8 c, it can be seen that the polarization potential of the symmetrical battery of the present invention is stable at about 80mV. Under the same conditions, the polarization potentials of the symmetrical batteries 1, 2, 3, 4, and 5 are about 500mV to 3V, which shows that the high entropy solid electrolyte material of the present invention has excellent cycle stability and the effect of inhibiting the growth of lithium dendrites as a lithium battery electrolyte. x (Fe 0.2 Co 0.2 Ni 0.2 Mn 0.2 Zn 0.2 ) The material structure stability of PS3 as a solid electrolyte for secondary lithium batteries was investigated. After 300h of charge and discharge cycles, the battery was disassembled, the solid electrolyte was removed, the residual lithium on the surface was cleaned with ethanol, dried and ground into powder, and then subjected to XRD and SEM tests. Fig. 9 a and Fig. 9 As shown in b, it can be seen that before and after charging and discharging, the high entropy metal sulfur phosphorus compound electrolyte material of the present invention does not change in substance and structure during the process of being used as a solid electrolyte for a secondary lithium battery, which further illustrates the excellent stability of the high entropy metal sulfur phosphorus compound electrolyte material of the present invention.

[0054] This embodiment only takes lithium-based batteries as an example for illustration. When the A element in the high entropy metal sulfide of the present invention is Na, K, Mg or Ca, it can be used as a solid electrolyte material having the performance of Na, K, Mg or Ca ion conduction, and can be used in sodium-based, potassium-based, magnesium-based or calcium-based batteries, respectively.

[0055] The foregoing description of specific exemplary embodiments of the present invention is for the purpose of illustration and demonstration. These descriptions are not intended to limit the present invention to the precise form disclosed, and it is clear that many changes and variations can be made based on the above teachings. The purpose of selecting and describing the exemplary embodiments is to explain the specific principles of the present invention and its practical application, so that those skilled in the art can realize and utilize various different exemplary embodiments of the present invention and various different selections and changes. The scope of the present invention is intended to be limited by the claims and their equivalents.

Claims

1. A high entropy metal sulfide phosphide electrolyte material, characterized in that: Obtained by sintering a raw material containing elements A, B, P and X, wherein A is selected from at least one metal element selected from IA and / or IIA, B is selected from at least four transition metal elements, or B is selected from at least three transition metal elements and at least one main group metal element or metalloid element, P is phosphorus, X is sulfur, and the molar ratio of A to B is between (1-4):(4-1); The transition metal element is selected from Ag, Au, Co, Cr, Cu, Fe, Hf, Mn, Mo, Nb, Ni, Pd, Rh, Ru, Sc, Ta, Ti, V, W, Y, Zn or Zr; the main group metal element is selected from Al, Sn, In or Bi; the metalloid element is selected from B, Ge or Si; The high entropy metal sulfide phosphide electrolyte material has a two-dimensional layer structure.

2. The high entropy metal sulfide phosphide electrolyte material according to claim 1, characterized in that: The A is at least one metal element selected from Li, Na, K, Mg or Ca.

3. The high entropy metal sulfide phosphide electrolyte material according to claim 1, characterized in that: The B is selected from the transition metal elements of the fourth and fifth periods in groups VIIB, VIII, IB and IIB; And / or, B is selected from five or more transition metal elements; And / or, the molar ratio of the P to the X is 1:(1-3).

4. The high entropy metal sulfide phosphide electrolyte material according to claim 3, characterized in that: The elements in B are in equal molar ratios.

5. The high entropy metal sulfide phosphide electrolyte material according to any one of claims 1 to 4, characterized in that The high entropy metal sulfide phosphide electrolyte material has a single crystal structure.

6. A method for preparing a high entropy metal sulfide phosphide electrolyte material according to any one of claims 1 to 5, characterized in that: include: The sintering step is to sinter the raw materials containing the elements A, B, P and X under vacuum or protective gas conditions to obtain the high entropy metal sulfide phosphide electrolyte material.

7. The preparation method according to claim 6, characterized in that: The raw material containing A is a metal salt or a simple substance, and the raw materials containing B, P and X are simple substances.

8. The preparation method according to claim 6, characterized in that: Before the sintering step, a grinding step is also included for grinding and mixing the raw materials.

9. The preparation method according to claim 8, characterized in that: The grinding method is ball milling.

10. The preparation method according to claim 6, characterized in that: In the sintering step, the sintering temperature is between 500°C and 1200°C; And / or, in the sintering step, the holding time at the sintering temperature is 10 hours to 100 hours.

11. The preparation method according to claim 10, characterized in that: The sintering temperature is between 700°C and 800°C; And / or, the holding time at the sintering temperature is 40h to 60h.

12. A battery, characterized in that: A high entropy metal sulfide phosphide electrolyte material comprising any one of claims 1 to 5.

13. The battery according to claim 12, characterized in that The battery is an all-solid-state battery.

14. An electronic or electrical device, characterized in that: A battery comprising the battery of claim 13.

Citation Information

Patent Citations

  • Solid electrolyte and preparation method thereof as well as electrochemical device and electronic device containing same

    CN109841898A

Cited By

  • Solid electrolyte material, preparation method thereof and battery

    CN116845340A